Correlates of Extent of Readiness of ESSU Faculty after its First Year of OB Curriculum Implementation - Estelita Madriaga; Ma. Caroll T. Arguelles; Jairus Ken Balagbis; Ronilo C. Caspe; Lea Nelly N. Abucay; Marion Nico Ronda; Melissa N. Abucay (Generasi Sains Indonesia, 2024)
This was a quantitative correlational research that evaluated the preparedness of the faculty at Eastern Samar State University after the first group of graduates in the K-to-12 Basic Education Program. A total of 139 members of the faculty were selected randomly as the sample of nine different colleges, i.e., the College of Arts and Sciences, the College of Agriculture and Natural Sciences, the College of Nursing and Applied Sciences, the College of Computer Studies, the College of Technology, the College of Education, the College of Business Management and Accountancy, and the College of Criminal Justice Education. Descriptive statistics (percentages and means) were used to acquire primary data. The correlation coefficient of Pearson was used to test the relationship between the independent variables (faculty profile characteristics) and the dependent variable (perceived professional readiness). The level of significance was fixed to α =.05 to accept or reject the null hypotheses. The results showed that the various variables of faculty profile, including the highest level of education, teaching years, attendance in training seminars and workload did not significantly relate to the perception that teachers held about their professional readiness.